Influence of gas detonation spraying parameters on the geometrical structure of Fe-Al intermetallic protective coatings - Chrostek, Tomasz; Bramowicz, Mirosław; Rychlik, Kazimierz; Wojtkowiak, Adam; Senderowski, Cezary (Technical Sciences, 2019)
The paper presents the results of an analysis of the geometrical structure of Fe-Al intermetallic protective coatings sprayed under specified gun detonation spraying (GDS) conditions. Two barrel lengths, two powder injection positions (PIP) at the moment of spark detonation, and two numbers of GDS shots with 6.66 Hz frequency were applied as variable parameters in the GDS process. Surface profile measurements were conducted by contact profilometry with the use of the TOPO-01 system and the Mitutoyo SJ 210 profilometer. The measured parameters were used to analyze surface topography in two-dimensional (2D) and three-dimensional (3D) systems. It was assumed that roughness can be regarded as a non-stationary parameter of variance in surface amplitude which is highly dependent on the sampling rate and spraying distance. Therefore, changes in surface amplitude parameters and functional properties were analyzed across segments with a length (ln) of 1.25, 4 and 12.5 mm. The development of the geometric structure of the surface was analyzed with the RMS (Root Mean Square) fractal method, and the geometric structure of the surface stretched by several orders of magnitude was evaluated based on the correlation between roughness (Rq), segment length (ln) and fractal dimension (D). The RMS method and the calculated fractal dimension (D) supported the characterization of the geometric structure of intermetallic Fe-Al protective coatings subjected to GDS under the specified process conditions based on the roughness profiles of surface segments with a different length (ln).